Imatinib protects against human beta-cell death via inhibition of mitochondrial respiration and activation of AMPK. Issue 19 (14th October 2021) - Elksnis, Andris; Schiffer, Tomas A; Palm, Fredrik; Wang, Yun; Cen, Jing; Turpaev, Kyril; Ngamjariyawat, Anongnad; Younis, Shady; Huang, Suling; Shen, Yu; Leng, Ying; Bergsten, Peter; et al.
Abstract: The protein tyrosine kinase inhibitor imatinib is used in the treatment of various malignancies but may also promote beneficial effects in the treatment of diabetes. The aim of the present investigation was to characterize the mechanisms by which imatinib protects insulin producing cells. Treatment of non-obese diabetic (NOD) mice with imatinib resulted in increased beta-cell AMP-activated kinase (AMPK) phosphorylation. Imatinib activated AMPK also in vitro, resulting in decreased ribosomal protein S6 phosphorylation and protection against islet amyloid polypeptide (IAPP)-aggregation, thioredoxin interacting protein (TXNIP) up-regulation and beta-cell death. 5-Aminoimidazole-4-carboxamide ribonucleotide (AICAR) mimicked and compound C counteracted the effect of imatinib on beta-cell survival. Imatinib-induced AMPK activation was preceded by reduced glucose/pyruvate-dependent respiration, increased glycolysis rates, and a lowered ATP/AMP ratio. Imatinib augmented the fractional oxidation of fatty acids/malate, possibly via a direct interaction with the beta-oxidation enzyme enoyl coenzyme A hydratase, short chain, 1, mitochondrial (ECHS1). In non-beta cells, imatinib reduced respiratory chain complex I and II-mediated respiration and acyl-CoA carboxylase (ACC) phosphorylation, suggesting that mitochondrial effects of imatinib are not beta-cell specific. In conclusion, tyrosine kinase inhibitors modestly inhibit mitochondrial respiration, leading to AMPK activation and TXNIP down-regulation, which in turn protects against beta-cell death.